Desain Penilaian (Assessment) Pendidikan Agama Islam - Ishaq, Muhammad; Sari, Nila (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Assessment is a fundamental component of the education system, including Islamic Religious Education (PAI). Through assessment, students’ progress and development can be measured, while also serving as a tool to evaluate the effectiveness of the learning process. This study employs a Systematic Literature Review method to analyze and synthesize various pieces of literature related to assessment design in PAI. The purpose of this study is to examine the concepts, objectives, functions, and techniques of comprehensive assessment within the context of Islamic education, with an emphasis on the affective (attitudinal) and psychomotor (skills) domains, in addition to the cognitive (knowledge) domain. The results of the review indicate that assessment in PAI functions not only as a tool for measuring academic achievement, but also as an instrument for shaping character, noble morals, and students’ piety. The functions of assessment include placement, selection, diagnosis, and feedback for improving the learning process. Several aspects that need to be considered in designing assessments include the selection of timing, targets, benchmarks, models, instruments, implementation techniques, data processing, and follow-up actions. The assessment techniques discussed include test techniques (such as objective written tests, essays, and oral tests) as well as non-test techniques (such as observation, interviews, and portfolio assessment). Performance assessment and attitude assessment are also explained as relevant approaches for evaluating the application of Islamic values in real-life behavior. By implementing a holistic assessment design, educators can more effectively monitor students’ spiritual, moral, and intellectual development, while also supporting the realization of the integral goals of Islamic education.